Safety and influence of a novel powder form of coconut inflorescence sap on glycemic index and lipid profile. (July 2020) - Mammen, Renny; John, Febi; Krishnakumar, I.M.; Maliakel, Balu; Mohanan, Ratheesh; Fleenor, Bradley
Abstract: Carbohydrates are the primary source of energy for human body. Carbohydrates increase resting muscle glycogen levels and help in delaying muscle fatigue. But, higher intake of high glycemic carbohydrates may lead to complications, if not balanced by physical activities. Our earlier studies have indicated that a proprietary powder preparation of coconut inflorescence sap (COCOZEN™, abbreviated as 'CSP' meaning 'coconut sap powder') contains relatively higher levels of micronutrients and possess antioxidant, anti-inflammatory, nephroprotective, hepatoprotective, gastroprotective and ergogenic activities. Thus, the present study was aimed to investigate the safety and efficacy of CSP (15 g/day for 90 days) on healthy and nonathletic subjects (n = 20). The study was performed in two phases. In the first phase, glycemic index (GI) was measured using glucose as a reference standard. In the second phase, CSP was supplemented at (15g × 1)/day dosage for 90 days and monitored the anthropometric parameters, adverse events, blood sugar levels (fasting and postprandial), blood pressure, and other routine hematological and biochemical parameters. It was observed that CSP possess a GI of 52.47 and is safe with an acceptable sensory attribute. It did not contribute any side effects or deviations in blood sugar or other hematological and biochemical parameters, except in Hb and lipid profile which showed significant (p < 0.05) enhancement. Graphical abstract: Image 1